2002
DOI: 10.1079/phn2001319
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between frequency of carbohydrates intake and dental caries: a cross-sectional study in Italian teenagers

Abstract: Objective: To propose an approach for investigation of the relationship between the frequency of carbohydrates intake and dental caries in real-life conditions. Design: The frequency of separate eating events (with the exclusion of lunch and dinner) and their sugars and starch content were assessed on the basis of diaries collected for seven consecutive days. The total number of decayed, missing and filled teeth (DMFT) was assessed through clinical examination. The interrelation between DMFT and frequency of e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
19
0
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 13 publications
5
19
0
2
Order By: Relevance
“…Among children of better socio-economic status, both in developing and developed nations, poor dental health seems to indicate overnutrition. DMFT may be interpreted as a proxy for energy intake, in line with the earlier studies [41,42], revealing that energy intake might be more important than energy expenditure. Regardless of socio-economic and cultural differences, economic developmental status, and countries' differing oral health care systems, family interaction patterns, in terms of family dinners and TV viewing habits, seem to have a positive effect on the dietary habits and dental health of pre-adolescents; these therefore may also affect obesity patterns.…”
Section: Resultssupporting
confidence: 83%
“…Among children of better socio-economic status, both in developing and developed nations, poor dental health seems to indicate overnutrition. DMFT may be interpreted as a proxy for energy intake, in line with the earlier studies [41,42], revealing that energy intake might be more important than energy expenditure. Regardless of socio-economic and cultural differences, economic developmental status, and countries' differing oral health care systems, family interaction patterns, in terms of family dinners and TV viewing habits, seem to have a positive effect on the dietary habits and dental health of pre-adolescents; these therefore may also affect obesity patterns.…”
Section: Resultssupporting
confidence: 83%
“…The biofilm was not mechanically disrupted by brushing and possible topical effects of dentifrice components on enamel did not occur. Nevertheless, the findings emphasize the relevance of fluoride use and give support to epidemiological studies in children [Karjalainen et al, 2001;Marshall et al, 2003] and adolescents [Arcella et al, 2002], showing that, when there is extensive fluoride exposure, dental caries is only associated with high frequency of sugar consumption.…”
Section: Discussionsupporting
confidence: 67%
“…Qin et al [2008] demonstrated that night feeding and excessive sugar intake were important contributors to the development of severe early childhood caries. Other studies suggested that sweets or beverage frequencies were independently associated with children with severe early childhood caries [Arcella et al, 2002;Marshall et al, 2005]. In Swedish 2-and 3-year-old children, eating at bedtime and during the night, in particular, was strongly correlated with severe early childhood caries.…”
Section: Discussionmentioning
confidence: 93%